CHALLENGES ASSOCIATED WITH MANAGEMENT OF TYPE 2 MELLITUS AMONG ADULTS AGED 45-60 YEARS ATTENDING DIABETIC CLINIC AT KISENYI HEALTH CENTRE IV IN KAMPALA DISTRICT. A DESCRIPTIVE CROSS-SECTIONAL STUDY DESIGN. - Kamoga , Arthur Ronald (Student's Journal of Health Research Africa, 2023)
Background: Type 2 diabetes mellitus is a type of diabetes mellitus that is very prevalent in Uganda and affects a wide percentage of the adult population. Much as there have been successive interventions in the prevention and control of this non-communicable disease, it is still increasing annually. Methodology: This was a descriptive cross-sectional study conducted to assess the challenges associated with the management of type 2 diabetes mellitus among adults aged 45-60years attending the diabetic clinic at Kisenyi Health Centre IV and the researchers ought to determine the knowledge, lifestyle factors, and health facility-related factors associated with the management of type2 diabetes mellitus among the same population. Results: Study findings revealed that males were the majority65% and stayed in a rural residence 69%. Most of the respondents had sufficient knowledge of diabetes mellitus. More than 80%had knowledge of the definition, types, signs, and causes of diabetes. The majority of respondents said there was a general readiness of facilities to handle diabetes but the health workers needed more training. Conclusion: In conclusion, the respondents had sufficient knowledge of diabetes mellitus. Most of the diabetics could define diabetes and knew at least two causes of diabetes mellitus though most thought that taking too much sugar was the most likely cause. The respondents know the types of diabetes mellitus, its signs and symptoms, and the susceptible ages of diabetes mellitus. Recommendations: There is a need for the government to therefore prioritize the non-communicable disease treatment and prevention budget, for the health facilities to develop better organizational structures in diabetic clinics and proper stock management. All these will help to reduce the diabetes disease burden in the country at large.